The prophets : introducing Israel's prophetic writings - Cook, Stephen L., 1962-; Strong, John T.; Tuell, Steven Shawn (Fortress Press, 2022)
The Prophets introduces students to the rise of prophecy in ancient Israel, the messages of individual prophets, the significance of the compositional history of the prophetic writings, and insights for interpreting the message of the prophets today. This textbook includes numerous images, charts, and maps to enhance the experience of the students.